Multiwave Structure of Traveling Ionospheric Disturbances Excited by the Tonga Volcanic Eruptions Observed by a Dense GNSS Network in China - Xiaolin Li; Feng Ding; Xinan Yue; Tian Mao; Bo Xiong; Qian Song (Space Weather)
Abstract We used dense global navigation satellite system data from China to track the propagation of traveling ionospheric disturbances (TIDs) triggered by the 2022 January 15 Tonga volcanic eruption. We identified two TIDs originating from the eruption. One, which has been reported widely by a number of recent investigations, had a velocity of ∼361 m/s. However, another long‐distance propagating TID with a velocity of ∼264 m/s has not been widely discussed. The velocities of these TIDs coincide with previous simulation results of gravity‐wave L0 and L1 modes. We propose that these TIDs were caused by the L0 and L1 ducted modes of gravity waves excited by the volcanic eruption. However, the L1 mode is usually negligible due to its weak amplitude in comparison with that of the L0 mode. The enormous energy release resulted in a stronger amplitude of the L1 mode, which induced a detectable TID in the ionosphere.